Real-Time Acoustic Phenomena Modelling for Computer Games Audio Engine - MIGA, Bartłomiej; ZIÓŁKO, Bartosz (Archives of Acoustics, 2015)
This article presents an efficient method of modelling acoustic phenomena for real-time applications such as computer games. Simplified models of reflections, transmission, and medium attenuation are described along with assessments conducted by a professional sound designer. The article introduces representation of sound phenomena using digital filters for further digital audio processing.